Rosacea understanding among Korean patients: A multi-center questionnaire study - Yu Ri Woo; Suyeun Kim; Sang Hyun Cho; Hei Sung Kim (Wolters Kluwer Medknow Publications, 2023)
Background: Rosacea is a common chronic skin condition. To manage rosacea long-term and prevent further flare-ups, patients need to be aware of the disease and have sound knowledge of the condition. However, few related studies have been conducted on this subject. Objectives: The aim of this study was to identify rosacea awareness and knowledge among Korean rosacea patients and their means of gathering information on the disease. Methods: A prospective multicenter cross-sectional study recruited a total of 201 outpatients who were diagnosed with rosacea by a dermatologist. All were asked to complete a questionnaire asking about their demographic characteristics, rosacea awareness, and knowledge. Results: Among 201 rosacea patients, 146 (72.6%) were unaware of the disease before their diagnosis. The median number of questions the patients correctly answered was 6 of a total of 13 questions (46%) on rosacea knowledge, implying relatively shallow knowledge on rosacea. Better understanding of rosacea was negatively associated with age (odds ratio [OR] 0.965; 95% confidence interval [CI]: 0.941 - 0.989) and positively associated with a higher education level (OR = 2.896; 95% CI: 1.379-6.082). Individuals with rosacea felt that they were getting reliable information from doctors (n = 189, 94%), followed by the Internet (n = 38, 18.9%). Conclusion: Overall, rosacea awareness and knowledge among Korean rosacea patients were relatively low. Detailed education, especially targeting elderly patients and those with low education levels, is necessary for better disease outcomes.